Understanding patients' views and willingness toward the use of telehealth in a cancer genetics service in Asia. Issue 6 (1st May 2021) - Sim, Jackie; Shaw, Tarryn; Li, Shao‐Tzu; Courtney, Eliza; Yuen, Jeanette; Chiang, Jianbang; Nazir, Maryam; Tan, Ryan; Ngeow, Joanne
Abstract: Telehealth is a growing field, its pertinence magnified by COVID‐19 causing the accelerated digitalization of the world. Given the significant global demand to provide telehealth services, it is important to explore patient receptiveness toward this alternative service model, particularly from regions where it has yet to be implemented. We conducted a cross‐sectional study to understand the views and willingness of patients toward the use of telehealth for cancer genetic counseling. A survey was completed by 160 patients of the National Cancer Centre Singapore, and descriptive statistics were used to analyze the data. The study found that 95.6% ( n  = 153/160) of participants did not have prior telehealth experience. Most participants were willing or neutral toward having genetic counseling by phone ( n  = 114/160, 71.3%) and video ( n  = 106/160, 66.3%). However, majority prefer in‐person appointments for first ( n  = 127/160, 79.4%) and follow‐up ( n  = 97/160, 60.6%) visits over telehealth. Majority agreed that a phone/video consultation would meet most of their needs but voiced concerns regarding privacy and sharing of information ( n  = 79/160, 49.4% for phone; n  = 74/160, 46.3% for video) and whether their emotional needs could be met ( n  = 61/160, 38.1%). Participants' age, employment status, income, mode of transportation to the appointment, and whether special arrangements were made to attend the in‐person appointment were associated with receptivity to telehealth genetic counseling ( p  ≤ .05 for all). This study adds diversity to existing literature and demonstrates that patients from Asia are generally willing and accepting of the use of telehealth in a cancer genetics service. This will help meet increasing global demand of telehealth consultations in the post‐pandemic new norm. Furthermore, it will also provide services for underserved populations and patients requiring urgent testing in a timely manner. Further studies are needed to explore the cost‐effectiveness and fair billing methods, as well as willingness and acceptability of telehealth genetic counseling in post‐COVID times.